T follicular regulatory (Tfr) cells: Dissecting the complexity of Tfr‐cell compartments. Issue 1 (15th March 2019) - Fonseca, Válter R.; Ribeiro, Filipa; Graca, Luis
Summary: Germinal centers (GC) have been known as key anatomic structures in humoral immunity, where isotype switching and affinity maturation occur. As a consequence, elucidation of GC regulation has potential implications for the understanding of autoantibody‐mediated diseases. It is now accepted that different regulatory mechanisms coexist, including the action of a specialized population of Foxp3 + regulatory T cells with unique access to the B‐cell follicle: the T follicular regulatory (Tfr) cells. Tfr cells develop through a multistep process requiring migration through different compartments of lymphoid tissues. This review discusses the ontogeny and physiology of Tfr cells, their distribution within distinct anatomic compartments, and their function. A greater understanding of Tfr biology and GC regulation is likely to lead to better stratification of patients with autoantibody‐mediated diseases, and to the identification of novel therapeutic targets.